Transient myocardial ischaemia after acute myocardial infarction. Issue 5 (November 1990) - Currie, P; Saltissi, S
Abstract : The prevalence and characteristics of transient myocardial ischaemia were studied in 203 patients with recent acute myocardial infarction by both early (6.4 days) and late (38 days) ambulatory monitoring of the ST segment. Transient ST segment depression was much commoner during late (32% patients) than early (14%) monitoring. Most transient ischaemia (greater than 85% episodes) was silent and 80% of patients had only silent episodes. During late monitoring painful ST depression was accompanied by greater ST depression and tended to occur at a higher heart rate. Late transient ischaemia showed a diurnal distribution, occurred at a higher initial heart rate, and was more often accompanied by a further increase in heart rate than early ischaemia. Thus in the first 2 months after myocardial infarction transient ischaemia became increasingly common and more closely associated with increased myocardial oxygen demand. Because transient ischaemic episodes during early and late ambulatory monitoring have dissimilar characteristics they may also have different pathophysiologies and prognostic implications.